1941
DOI: 10.1042/bj0350595
|View full text |Cite
|
Sign up to set email alerts
|

The enzymic decarboxylation of oxaloacetate

Abstract: ALTHOUGH oxaloacetate has an important role in cellular metabolism, no enzyme has been described which brings about a rapid decarboxylation of the acid. Breusch [1939] investigated a heat-stable component of mammalian tissue responsible for this decarboxylation but could not identify it with any known physiological agent. The rate of this decarboxylation is comparatively slow. In investigations on the utilization of CO2 by bacteria, Wood & Werkman [1938; 1940] postulated the reverse reaction, i.e. the carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1942
1942
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…Oxalacetate is decomposed enzymatically t o pyruvate and COz (1)(2)(3)(4)(5). T h e decarboxylation also occurs non-enzymatically by spontaneous and metal-catalyzed processes (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Oxalacetate is decomposed enzymatically t o pyruvate and COz (1)(2)(3)(4)(5). T h e decarboxylation also occurs non-enzymatically by spontaneous and metal-catalyzed processes (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, PNA-esterase activity is not enhanced by metal ions (e.g. Mn2, Mg21, Zn2) which in several cases are neccessary for enzymatic decarboxylation [23,24]. Moreover no inhibition of the enzyme is observed in presence of EDTA, which is a typical inhibitor of metal ion dependent decarboxylases [241.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was proposed by Menkel et al (29) and was indicated by overexpression of the pyruvate carboxylase gene (40), inactivation of PEP carboxykinase (46), inactivation of citrate and methylcitrate synthases (45), and disruption of the malate:quinone oxidoreductase gene (31). However, there have not been many studies addressing the role of oxaloacetate decarboxylase (ODx), an enzyme that has high levels of activity in different C. glutamicum strains (21) and catalyzes the irreversible decarboxylation of oxaloacetate (25), at this key branch point.…”
mentioning
confidence: 99%